Conversion of Rice Husk into Amorphous Silicon Dioxide Using Taguchi’s Method - Wan Rozuhan, Wan Nur Hamizah (IRC, 2017)
The properties of amorphous silicon dioxide are very attractive and by having these promising properties, amorphous silicon dioxide is highly significant as it is widely used in many applications. This research emphasizes on the influence of processing parameters of mechanical milling time, heating temperature, heating rate and heating time on the formation of amorphous silicon dioxide (SiO2) using rice husk (RH) as the starting precursor by using Taguchi’s method. The objectives of this research are to evaluate the effects of mechanical milling time, processing temperature, heating time and heating rate on the production of amorphous silicon dioxide and to evaluate the most significant parameters in the synthesis of amorphous silicon dioxide by using Taguchi’s method. In this research, Taguchi’s method was applied where the total number of experiments conducted is nine (9) at three (3) level. There were three (3) milling time that were used; 180 minutes (mins), 240 minutes and 300 minutes by using a ball mill. A total of three (3) processing temperature were used for the heat treatment process which were 950⁰C, 1000⁰C and 1050⁰C while the heating rate varied from 5⁰C/min, 10⁰C/min and 15⁰C/min. The combustions were conducted at various time of 60 mins, 120 mins and 180 mins by using heat treatment furnace. The morphology of the products was analyzed by using SEM and the contribution of each factor was determined using Analysis of Variance (ANOVA). The important factors influencing the synthesis of amorphous silicon dioxide are milling time, followed by heating rate, temperature and heating time. The most significant process parameters for the synthesis of amorphous silicon dioxide were obtained with parameters of A2, B3, C1 and D3; i.e. temperature of 1000⁰C, milling time of 300 mins, heating time of 60 mins and heating rate of 15⁰C/min. The most significant process parameters of A2, B3, C1, D3 produced 1.044 gram of amorphous silicon dioxide which is within 95% confidence interval of the expected yield from most significant process parameters; i.e. 1.068 gram.